Intuition, Creativity, Innovation - Samier (Wiley-ISTE, 2019)
This book explores the scientific perspective on the concept of intuition, particularly in relation to vibration, music and emotion. Taking a multimedia approach, it contains practical exercises that will help the reader to achieve greater intuition and develop their capacity for creativity and innovation. The exercises in this book come from over a hundred workshops worldwide in both business and higher education. They include, for example, the "Mind Map of Me", an introspective exercise designed to develop trust and confidence in the self and the reader's own intuition. The book opens the field of possibilities to the reader, offering encouragement and motivation to explore new approaches and techniques. With these tools, intuition can become a valuable ally in everyday life.